2018
DOI: 10.1128/jvi.00404-18
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Transport Enables Neuron-to-Neuron Propagation of Human Coronavirus OC43

Abstract: Human coronaviruses (HCoV) are recognized respiratory pathogens for which accumulating evidence indicates that in vulnerable patients, the infection can cause more severe pathologies. HCoVs are not always confined to the upper respiratory tract and can invade the CNS upon still unclear circumstances. HCoV-induced neuropathologies in human are difficult to diagnose early enough to allow therapeutic interventions. Making use of our already described animal model of HCoV neuropathogenesis, we describe the route o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
432
2
28

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 426 publications
(475 citation statements)
references
References 77 publications
13
432
2
28
Order By: Relevance
“…HCoV-OC43, a respiratory CoV, could be a powerful tool for gaining new insights into the neurological manifestations and neurotropic mechanisms of other respiratory viruses. In the present study, our data demonstrated that rOC43-ns2DelRluc levels reflected HCoV-OC43-WT replication in the brain and its spread to the spinal cord of living mice, with bioluminescence intensity directly correlating with viral loads as measured by IFA and western blot and consistent with previous studies (Dubé et al, 2018;Jacomy et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HCoV-OC43, a respiratory CoV, could be a powerful tool for gaining new insights into the neurological manifestations and neurotropic mechanisms of other respiratory viruses. In the present study, our data demonstrated that rOC43-ns2DelRluc levels reflected HCoV-OC43-WT replication in the brain and its spread to the spinal cord of living mice, with bioluminescence intensity directly correlating with viral loads as measured by IFA and western blot and consistent with previous studies (Dubé et al, 2018;Jacomy et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…2A, upper), whereas low viral RNA levels were detected in the hearts and spleen, and extremely low levels were detected in the blood ( Fig. 2A, lower), consistent with previous reports on HCoV-OC43-WT (Dubé et al, 2018;Jacomy and Talbot, 2003). Immunostaining of brain and spinal cord sections from mice that underwent intracerebral infection confirmed the presence of rOC43-ns2DelRluc ( Fig.…”
Section: Roc43-ns2delrluc Replication and Dissemination In Mice Withsupporting
confidence: 90%
“…Furthermore, based on more recent work [269], Figure 1 illustrates the olfactory route, which is clearly the main route of neuroinvasion used by HCoV-OC43, as well as the early steps of subsequent neuropropagation within the CNS in susceptible mice and recapitulates the suggested equivalent pathway in humans. Nevertheless, our data suggest that HCoV-OC43 may also invade the CNS from the external environment through other pathways involving other cranial peripheral nerves [269], reminiscent of what was shown for other human respiratory viruses such as RSV and influenza virus [8]. Therefore, on the one hand, an apparently innocuous human respiratory pathogen such as the HCoV may reach the CNS by different routes and induce short-term illnesses, such as encephalitis.…”
Section: Possible Mechanisms Of Hcov Neuroinvasivenessmentioning
confidence: 97%
“…Experimental intranasal infections of susceptible mice also indicate that, once it has invaded the CNS, the virus disseminated to several regions of the brain and the brainstem before it eventually reaches the spinal cord [266][267][268]. Furthermore, based on more recent work [269], Figure 1 illustrates the olfactory route, which is clearly the main route of neuroinvasion used by HCoV-OC43, as well as the early steps of subsequent neuropropagation within the CNS in susceptible mice and recapitulates the suggested equivalent pathway in humans. Nevertheless, our data suggest that HCoV-OC43 may also invade the CNS from the external environment through other pathways involving other cranial peripheral nerves [269], reminiscent of what was shown for other human respiratory viruses such as RSV and influenza virus [8].…”
Section: Possible Mechanisms Of Hcov Neuroinvasivenessmentioning
confidence: 99%
See 1 more Smart Citation